Bantuan Hukum dan Implementasi Perlindungan HAM di Indonesia - Wadi, Fajrul (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2010)
One of the most actual issues nowadays is about the maintenance and protection of human rights moreover in a developing county, even in a poor country. The maintenance towards human rights is a kind of every human’s responsibility, it is not only a duty for the government but also it is a part of the duty for all societies. For this case, giving a judicial help for the victims of the human rights abuses by some lawyers is a kind of an implementation from the functions and purposes of judicial helps. Without the roles of giving the judicial helps for the victims of the human rights abuses, then it may cause an injustice for the protection of human rights moreover in Indonesia. As we know if our country Indonesia actually has a good system of the regulation about human rights, thus we only need to have any efforts as the implementation.